USE OF FRESH TECHNIQUE IN TEACHING WRITING DESCRIPTIVE TEXT TO THE EIGHTH GRADE STUDENTS OF SMP PGRI SUKAMORO - Nita Ria; Ratih Novtapianti (Jurnal Didascein Bahasa, 2019)
Writing is one of important skills to transfer knowledge between teacher and students. The objective of the study was to find out whether or not there was any significant differenceon writing achievement between the students who were taught by using FRESH technique in writing descriptive text and those who were not. The population of the study was the eighth grade students of SMP PGRI Sukamoro in academic year 2017/2018. The purposive sampling was used on this study. In conducting the study, the writers did experimental method by using quasi-experimental design to the two groups of students. Class VIII 1 became the experimental group and VIII 2 became the control group. The two classes were chosen because they had same level of competency in learning English. Instrument for collecting the data wastest.The result of the data showed that the mean score of post-test of experimental group was 74.11 and post-test of control group was 59.75.It means that there was a significant difference on writing achievement between the students who were taught by using FRESH technique in writing descriptive text and those who were not.